2016
DOI: 10.1177/1744987116649636
|View full text |Cite
|
Sign up to set email alerts
|

Using mixed methods to understand the healing trajectory for rural Irish women years after leaving abuse

Abstract: Research on effectiveness and satisfaction with domestic violence (DV) services is aimed at women who have accessed these services, leaving us little information about those who believe they cannot or choose not to do so. In addition, this research focuses exclusively on the structural barriers to access of information, or navigating systems to escape the abusive situation. Few studies have examined the sociocultural barriers to help seeking, either for escape from violence or for healing after safety has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 36 publications
0
36
1
Order By: Relevance
“…Although the physical and mental impact of GBV both generally and in specified forms has been well documented (see Heise et al, 2002, for review), many women choose not to disclose or seek help for their GBV experiences (Fugate, Landis, Riordan, Naureckas, & Engel, 2005; Saint Arnault & O’Halloran, 2016). For example, in a multinational survey of 42,000 women across 28 European Union Member States, it was found that help-seeking rates for GBV ranged from 4-27% depending on the country (European Union Agency for Fundamental Rights, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the physical and mental impact of GBV both generally and in specified forms has been well documented (see Heise et al, 2002, for review), many women choose not to disclose or seek help for their GBV experiences (Fugate, Landis, Riordan, Naureckas, & Engel, 2005; Saint Arnault & O’Halloran, 2016). For example, in a multinational survey of 42,000 women across 28 European Union Member States, it was found that help-seeking rates for GBV ranged from 4-27% depending on the country (European Union Agency for Fundamental Rights, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a multinational survey of 42,000 women across 28 European Union Member States, it was found that help-seeking rates for GBV ranged from 4-27% depending on the country (European Union Agency for Fundamental Rights, 2014). Reasons why survivors were not seeking help from formal resources included the perception that violence was “normal/not serious,” feeling burdened by their symptoms, emotional investment in the relationship, protecting the children, and shame (Fugate et al, 2005; Murray, Crowe, & Overstreet, 2015; Saint Arnault & O’Halloran, 2016). Other reasons included believing they should “deal with it alone,” feeling frozen, and feeling internalized stigma, manifesting as feelings of weakness, helplessness, or blame (Fugate et al, 2005; Murray et al, 2015; Saint Arnault & O’Halloran, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…One characteristic of this limitation can be viewed as a methodological one, which includes the combined issues of self-definition, definitions of trauma, and definitions of healing. There have been qualitative studies illuminating healing processes (Herman, 1997; Saint Arnault and O’Halloran, 2014, 2016; Sinko et al, 2019; Sinko and Saint Arnault, in press). This research describes healing and recovery experiences as generally including managing memories and emotions, integration of experiences into one’s self-definition, connecting with others and connecting with that which is larger than oneself, such as spirit, nature, or God.…”
Section: Introductionmentioning
confidence: 99%
“…Normativeness is thereby a belief system that is established in context to one's environment over time and that categorizes certain actions and behaviors as "normal" within that context (Raghaven et al, 2006). One is unlikely to seek help and support for those actions and behaviors largely because the process of seeking help is initiated by the perception that one's situation or condition is abnormal, severe, and/or signifies need (Saint Arnault, 2009;Saint Arnault & O'Halloran, 2016). The determination of need is based on a rational set of decisions by the individual, who, based upon her circumstance, weighs the potential gain that help would provide (Mechanic, Ettel, & Davis, 1990).…”
Section: Trauma Normativeness and Help Seekingmentioning
confidence: 99%